PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENCARIAN ALAMAT PENTING DI KOTA PADANG MENGGUNAKAN APLIKASI MOBILE - Ayu Fatimah; Titi Sriwahyuni; Nurindah Dwiyani (Universitas Negeri Padang, 2014)
This projects aims to provide an information system to search for the important address in Padang. The important address in Padang still use the phone book (yellow pages), but not everyone can use and have it. In the search for the important address in Padang, not everyone has a mobile phone that can access the internet and if using a mobile phone, it will need the charge. As well as in the search for important addresses in Padang, not everyone can call the operator, and call the operator also takes the charge. Because of that problem, this application created with no internet service, so it does not cost money. This mobile application system can provide information such as text display with detailed address and phone numbers and addresses an important route in Padang. The starting address point is from Padang’s Market because a lot of public transport with the important addresses major roads in Padang is passing along this way. The mobile application comes with a list of important address like Mosques, Hospitals, Hotels, Universities and Government Offices which contain such as info address, phone number and the address route to search the important address for the application’s user. This is an implementation on mobile phone based on java language programming with jar extension file. Keywords : Information Systems, Mobile Application, Addresses, Java .